THE EFFECT OF TEACHER’S CREATIVITY ON NATIVE INDONESIAN STUDENTS’ SUCCESS IN LEARNING CHINESE LANGUAGE - Febi Nur Biduri (IAIN MADURA, 2017)
Creativity is the ability of a person to produce something new; in the form of ideas or real works that are relatively different from what has been existed before. The problem formulated in this study is: Does the teacher's creativity have an effect on the success of learning Chinese as a foreign language? This research aims to: 1. Know the effect of the teacher's creativity on the success of learning Chinese language in the classroom, and 2. know the types and functions of the teacher's creativity to the Chinese learning process in the classroom. This research is useful for providing information about types and definition of creativity as well as what effect is drawn by a creative teacher to the learning process in the classroom. This research will also make it easier for the teacher to teach the Chinese language more creatively and appealingly. The research method used is descriptive qualitative that describes the situations that occurred in the classroom when the learning is going on with the creative teacher. The study was conducted in the Chinese Language subject in semester 8 at Japanese Literature Faculty of Darma Persada Universitas, Jakarta. The data collected were from observation, interview, and questionnaire.